Longitudinal monitoring of mRNA-vaccine-induced immunity against SARS-CoV-2 - Monzon-Posadas, Werner O.; Zorn, Jasmin; Peters, Kathrin; Baum, Maximilian; Proksch, Hannah; Schlüter, Celina Beta; Menting, Tanja; Pušnik, Jernej; Streeck, Hendrik (Frontiers in Immunology, 2023)
Worldwide vaccination campaigns significantly reduced mortality caused by SARS-CoV-2 infection and diminished the devastating effects of the pandemic. The first approved vaccines are based on novel mRNA technology and elicit potent immune responses offering high levels of protection from severe disease. Here we longitudinally assessed adaptive immune responses during a 12-month follow-up period after the initial immunization with 2 doses of mRNA vaccines and after the booster dose in blood and saliva. Our findings demonstrate a rapid waning of the anti-spike IgG titers between months 3 and 6 after the initial vaccination (1.7- and 2.5-fold decrease in plasma and saliva, respectively; P<0.0001). Conversely, the frequency of spike-specific memory B cells increased during this period (2.4-fold increase; P<0.0001) while the frequency of spike-specific CD4+ and CD8+ T cells remained stable for all assessed functions: cytotoxicity, IFNγ, IL-2, and TNFα expression. Booster vaccination significantly improved the antibody response in plasma and saliva, with the most profound changes observed in the neutralization capacity against the currently circulating omicron variant (25.6-fold increase; P<0.0001). The positive effect of booster vaccination was also evident for spike-specific IgG+ memory B cell (2.4-fold increase; P<0.0001) and cytotoxic CD4+ and CD8+ T cell responses (1.7- and 1.9-fold increase respectively; P<0.05). Collectively, our findings offer a detailed insight into the kinetics of adaptive immune response following SARS-CoV-2 vaccination and underline the beneficial effects of a booster vaccination.